Subjective Well-Being of Working Mothers: A Photovoice Study - RATU, FERONIKA; Pello, Shela Christine; Damayanti, Yeni (Journal of Health and Behavioral Science, 2024)
Working mothers are required to take care of household chores, educate children, and complete tasks at work. The dual role will affect the subjective well-being of working mothers. The subjective well-being aspects studied were global life satisfaction and life satisfaction in specific domains, especially the work and family domains. This study aims to identify the subjective well-being of working mothers. This research is a qualitative study that uses the photovoice data collection method. The inclusion criteria are working mothers with permanent jobs, children under 10 years of age, living in Kupang City, and being willing to become research participants. There were 6 participants involved in this study. The results of this study found four main themes related to the subjective well-being of working mothers: social relationships, affective factors, satisfaction in work life, and satisfaction in home life. It is suggested that working mothers develop positive effects in work and home life and that future researchers be able to examine the psychological well-being of working mothers.